Characterizing the cellular latent reservoir of HIV-1 and the effect of immune activation on characteristics of the reservoir - Ismail, Sherazaan Dineo (Department of Clinical Laboratory Sciences, 2022)
Since the advent of antiretroviral therapy (ART) and the resultant suppression of viraemia in the majority of people living with HIV-1 (PLWH) on ART, HIV-1 infection has become manageable and PLWH have similar life expectancies as uninfected persons. However, ART is not curative, is needed lifelong, and its cessation leads to the recrudescence of viraemia. This is due to the formation of a latent reservoir that is long-lived and stable over time, precluding HIV-1 cure. The factors affecting reservoir formation, establishment, and kinetics are not fully understood. Furthermore, differences exist at the population level in disease progression in PLWH depending on ethnicity, biological sex, and infecting viral subtype. Similarly, differences in the latent reservoir of HIV-1 have been described, although less extensively. Understanding what shapes the latent HIV-1 reservoir is critical for developing strategies for cure. Furthermore, it is imperative that cure research is undertaken in diverse populations to ensure coverage of knowledge across different demographics. The latter will ensure that a cure strategy can be developed that will be globally implementable. In the Introductory chapter of this thesis, I provide a detailed review of the current literature and address the need for cure research in low-and middle- income countries. If a global cure is to be achieved, the burden of HIV-1 will need to be addressed in many different populations, most notably African women, as women bear the burden of HIV-1 globally. In South Africa, the country in the sub-Saharan African region with the highest prevalence of HIV-1, women are roughly twice as likely to be living with HIV than men (aged 15 to 49), with a prevalence rate 6% higher than the national average of 19%. Since women are underrepresented in HIV-1 research in general and more specifically in cure studies due to the paucity of research in countries outside of the global North, reservoirs and cure strategies ii need to be characterized in this context. Furthermore, while early treatment is the WHO standard of care for people diagnosed with HIV, a large majority of PLWH only initiated treatment in chronic infection. Since early ART is known to restrict formation of the latent reservoir of HIV-1, research in both early and late ART initiators is necessary. This research focused on characterising the viral reservoir in South African women in a well-established cohort of women who were recruited during acute HIV infection and followed until treatment initiation (which occurred during chronic infection) and beyond. Overall, this thesis focuses on characterising immune activation and inflammation during the course of both untreated and treated HIV-1 infection in a cohort of South African women and subsequently determining whether clinical or immune measures influence characteristics of the latent reservoir of HIV-1. T cell activation and the levels of soluble inflammatory cytokines in plasma were determined in forty-six women in the CAPRISA 002 Acute infection cohort. Chapter 2 describes the cellular immune activation and inflammation profiles of these participants throughout the course of infection at the following timepoints: acute infection, oneyear post-infection, and within a year preceding ART initiation, and two- and four- years postART initiation. T cell activation peaked in chronic infection and reduced dramatically after ART initiation. CD4+ and CD8+ T cell activation reached a post-treatment nadir by two years after ART initiation. Cytokine measures were within the ranges reported in the literature for PLWH. Notably CXCL-10 levels in plasma decreased significantly between two- and four years post-ART, indicating that it may be a sensitive marker of ongoing systemic inflammation in people on ART. In short, the T cell activation and inflammation profiles of the women in this study reflected what has been observed in other cohorts. iii The size of the replication-competent HIV-1 reservoir, measured by quantitative viral outgrowth assay after 5 years of suppressive antiretroviral therapy (ART), was quantified in twenty women of the cohort. In Chapter 3, the clinical and immunological correlates of reservoir size were investigated. Predictive modelling showed that the size of the replicationcompetent reservoir is directly related to viral load and CD4+ T-cell counts over the course of infection, although these measures do not fully predict reservoir size. We found that, in addition to viral load and CD4+ T-cell count, CD8+ T-cell activation within the year preceding ART, nadir CD4+ T-cell count, and baseline as well as on-treatment CD4:CD8 ratio at the time of sizing was associated with replication-competent reservoir size. We provide evidence that the late CD8+ T-cell activation level before treatment, together with viral loads and CD4+ T-cell counts, are directly related to the size of the replication-competent reservoir of HIV-1. Our results are consistent with the hypothesis that the host immune milieu near the time of ART initiation plays an important role in shaping the durable reservoir of HIV infection that persists on ART. Another characteristic of the HIV-1 reservoir is persistence: the presence of all forms of HIV1 within cells and tissues that contribute to pathogenesis, including defective, non-induced, and non-integrated forms of HIV-1. In Chapter 4, total HIV-1 DNA levels were measured as a proxy for viral persistence in thirty-one participants, and the correlates thereof investigated. The HIV-1 DNA levels in this cohort were similar to those reported in the literature for other cohorts where participants initiated therapy in late chronic infection. HIV-1 DNA levels did not differ significantly between two- and four years post-ART, but there was a trend to lower HIV-1 DNA when measuring pol versus gag gene frequencies in peripheral blood mononuclear cells (PBMC). These findings indicate that HIV-1 DNA decay rates may differ depending on the gene being measured, even when using the same assay. A weak significant correlation was iv found between CD4+ T cell counts at ART initiation and the change in HIV-DNA levels between two-and four years on ART. There was a significant correlation between residual CD4+ T cell activation at four years post-ART initiation and gag copies per million PBMC. A trend towards a correlation was found between CD4+ T cell activation and pol copies per million PBMC at the same timepoint. Finally, we found significant correlations between several cytokines at one-year post-infection and within one year pre-ART. These findings further solidify the hypothesis that the immune milieu around the time of ART initiation and after may play a complex role in formation of the viral reservoir of HIV-1. Our studies show a significant link between chronic immune activation and replication competent reservoir size, and also ongoing immune activation and viral persistence on ART. Further studies into whether these immune measures affect the timing of establishment and clonality of the reservoir in this cohort are ongoing and will inform the field about whether differences in cure strategies will need to be explored for those PLWH who had high levels of chronic immune activation before treatment initiation and subsequent shaping for the long-lived viral reservoir.